2001
DOI: 10.1302/0301-620x.83b5.0830676
|View full text |Cite
|
Sign up to set email alerts
|

The effect of preoperative donation of autologous blood on deep-vein thrombosis after total hip arthroplasty

Abstract: We have assessed the effect of the donation of autologous blood and the preoperative level of haemoglobin on the prevalence of postoperative thromboembolism in 2043 patients who had a total hip arthroplasty. The level of haemoglobin was determined seven to ten days before surgery and all patients had venography of the operated leg on the fifth postoperative day. The number of patients who had donated autologous blood (1037) was similar to that who had not (1006). A significant decrease in the incidence of dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Indeed, several variables associated with vascular events in this analysis including age, ethnicity and comorbidities, have been linked to increased body iron stores as well19. Alternatively, red cell transfusions, by increasing the circulating red cell mass, may improve hemostasis, with one consequence being an increased risk of thrombosis20. Stored red cells are severely depleted in nitric oxide, which may lead to vasoconstriction and increase the risk of thrombosis due to vascular rheologic changes and increased platelet activation21.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, several variables associated with vascular events in this analysis including age, ethnicity and comorbidities, have been linked to increased body iron stores as well19. Alternatively, red cell transfusions, by increasing the circulating red cell mass, may improve hemostasis, with one consequence being an increased risk of thrombosis20. Stored red cells are severely depleted in nitric oxide, which may lead to vasoconstriction and increase the risk of thrombosis due to vascular rheologic changes and increased platelet activation21.…”
Section: Discussionmentioning
confidence: 97%
“…The protocol aims at reducing the patient's unnecessary exposure to potent anticoagulants and their associated risks. Multimodal thromboprophylaxis encompasses [7][8][9][10][11]: preoperative VTE risk stratification; discontinuation of procoagulant medications and autologous blood donation [12]; surgery performed under regional hypotensive anaesthesia; intravenous administration of heparin during surgery and before femoral preparation [in total hip arthroplasty (THA) recipients]; aspiration of intramedullary contents; pneumatic compression; knee-high elastic stockings; and early mobilisation and chemoprophylaxis for 4-6 weeks. The preferred postoperative adjuvant chemoprophylaxis in patients with a low VTE risk is aspirin.…”
Section: Introductionmentioning
confidence: 99%
“…Most prospective, randomized clinical trials of VTE prophylaxis address pharmacological approaches, but the nonpharmacological approaches, listed in Table 19.5, can also have a major impact on VTE risk [17,[47][48][49]. For example, small prospective controlled trials have demonstrated that intermittent pneumatic compression (plus aspirin) is effective in preventing VTE following knee replacement surgery [49][50][51], and a retrospective trial demonstrated that patients who underwent autologous blood donation had a 30 % lower rate of DVT following hip replacement surgery [17].…”
Section: Prevention Of Vte Nonpharmacological Approachesmentioning
confidence: 99%
“…For example, small prospective controlled trials have demonstrated that intermittent pneumatic compression (plus aspirin) is effective in preventing VTE following knee replacement surgery [49][50][51], and a retrospective trial demonstrated that patients who underwent autologous blood donation had a 30 % lower rate of DVT following hip replacement surgery [17].…”
Section: Prevention Of Vte Nonpharmacological Approachesmentioning
confidence: 99%
See 1 more Smart Citation